Analyst forecasts during the COVID-19 pandemic: Evidence from REITs - Paul M. Anglin; Jianxin Cui; Yanmin Gao; Li Zhang (Journal of Risk and Financial Management, 2021)
The COVID-19 pandemic disrupts capital markets and confuses decision makers. This event represents an opportunity to better understand how financial analysts forecast earnings. We focus on forecasts for Real Estate Investment Trusts (REITs) in the United States, since REITs are relatively transparent during normal times, and since the real estate sector, as a whole, displays wide variations in forecasts during the pandemic. Using data between October 2018 and November 2020, our regression analysis finds that the severity of the pandemic increases analysts' forecast error and dispersion. Government interventions have an offsetting effect, which is relevant during the more severe times. These results are robust to various measures of the severity of the pandemic. We also find that the pandemic has differential effects across property types, where forecast error rises by more, for REITs, when focusing on Hospitality and Industrial properties, and dispersion rises by more, for REITs, when focusing on Hospitality, Retail, and Technology properties.
Keywords: G17; G01; D84; 330; analysts; COVID-19; earnings; forecast; information environment; pandemic; REITs